Improving Student Activities and Learning Achievements Through Picture Props for Math Subjects Counting Circumference - Sugiarto, Iwan (Universitas Sebelas Maret, 2020)
This classroom action research aims to improve motivation and learning outcomes of mathematics in calculating the perimeter of a square or square through the use of image media for third grade students at SDN Kebonagung in the second semester of SD Negeri Kebonagung in the 2019/2020 academic year. The research uses 2 cycles, analytical techniques. data using a comparative descriptive technique. The results of classroom action research through the use of image media concluded that the motivation and learning outcomes of mathematics in calculating the perimeter of a square or square for third grade students at SDN Kalipucang in the second semester of 2019/2020 increased. Second: The average value from the initial condition 59 to cycle 1 increased by 24% to 63.Third: The average value from cycle 1, 63 to cycle 2 increased 17% to 80.Fourth; The average value from the initial condition of 59 to the final condition increased by 21% to 80. The results of this study are expected to be useful for improving the quality of education, especially in SDN Kebonagung, Jatibarang District, Brebes Regency.